A longitudinal examination of the interpersonal theory of suicide for predicting suicidal ideation among LGBTQ+ youth who utilize crisis services: The moderating effect of gender. Issue 5 (22nd June 2021) - Chang, Cindy J.; Feinstein, Brian A.; Fulginiti, Anthony; Dyar, Christina; Selby, Edward A.; Goldbach, Jeremy T.
Abstract: Introduction: Despite high rates of suicide among LGBTQ+ youth, the interpersonal theory of suicide (IPTS) has rarely been examined in this population. The current study utilized a longitudinal design to examine whether perceived burdensomeness and thwarted belongingness independently and simultaneously predicted higher levels of suicidal ideation over time in a sample of LGBTQ+ youth who utilized crisis services. We also investigated whether gender identity moderated these associations. Methods: A total of 592 youth (12–24 years old) who had contacted a national crisis hotline for LGBTQ+ youth completed two assessments 1‐month apart. Results: Perceived burdensomeness and thwarted belongingness independently predicted greater suicidal ideation 1 month later; however, only perceived burdensomeness remained prospectively associated with suicidal ideation when both factors were tested in the same model. Gender identity moderated the associations between IPTS factors and suicidal ideation, such that both perceived burdensomeness and thwarted belongingness were associated with greater suicidal ideation 1 month later for sexual minority cisgender young women and transgender/genderqueer individuals, but not for sexual minority cisgender young men. Conclusion: The IPTS helps explain increases in suicidal ideation over time among LGBTQ+ youth and therefore can be used to inform suicide prevention and intervention approaches for this population.